ServQual Model Test on Teacher Education Program (PPG) Management: An Empirical Survey of Service Quality and PPG Student Satisfaction at Widya Dharma University, Klaten - Purwo Haryono; Arif Julianto Sri Nugroho; Iswan Riyadi; Tukiyo Tukiyo; Tasari Tasari (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The aim of the research was to analyze the index model of PPG FKIP Unwidha student satisfaction from the quality of online learning services by analyzing the gaps in each element of service. The research method used was in the form of quantitative research to test the gap between expectations and perceptions of service quality. Respondents in the research were 60 students. The sampling technique was carried out by purposive sampling. Quantitative tests in research were in the form of validity test, instrument item reliability, Servqual model gap test. Research findings show that all dimensions tested have a positive satisfaction value with the largest positive value on the empathy dimension. Lecturers and education staff at the Unwidha PPG Program must be able to improve service quality with priority improvements starting with the lowest positive value respectively on the next positive value.